Reconnection strategies of physical landscape: a case study in the Faculty of Sustainable Agriculture - Shahida Mohd Sharif; Izyan Ayuni Mohamad Selamat; Siti nurulhidayah zakaria (IDEAS, 2015)
The Landscape Development Plan of the Faculty of Sustainable Agriculture (FSA) aims to adopt the sustainable design strategies and environmental stewardship which can initiate reconnection with nature as well as to improve the well-being of its community. A pilot study was conducted at the faculty’s farm administration building to evaluate the foundation towards the formulation of a landscape design featuring reconnection of the major systems of physical landscape; air, water and land. Application of sustainable landscape design strategies were pre-tested on the campus ground which include soil amelioration, rainwater harvesting and selection of drought-tolerant plants. The farm administration building was chosen as it is frequently visited by the faculty members and visitors. It reflects the faculty’s aim to demonstrate to the wider public the application of sustainable practices as well as to encourage collaborative monitoring and maintenance of the landscape. The envisioned design is in response to the opportunities and ideas to improvise functionality and aesthetic appeal of the site.